1981
DOI: 10.1152/ajpgi.1981.240.5.g365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylprednisolone on electrolyte transport by in vitro rat ileum

Abstract: Administration of the glucocorticoid methylprednisolone (MP) (30 mg/kg body wt for 3 days) to rats increased intestinal mucosal guanylate cyclase and Na-K-ATPase activities, short-circuit current (Isc), electrical potential difference (PD), net Na absorption, and net Cl secretion and reversed HCO3 transport from secretion to absorption. In the MP-treated animals, removal of HCO3 from both the mucosal and serosal bathing solutions increased Cl secretion but did not alter the Isc, PD, and net Na flux. Removal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…With respect to Na transport and IS.,) these findings agree withl previous in vivo observations on rat ileum (2). A comiparable in vitro study with rat ileum (20) differs with both in vivo rat data and our in vitro rabbit data; although MP treatment was found to increase net Na absorption, it was also found to stimulate net Cl secretion; MP treatment was also reported to increase mucosal cGMP concentration, suggesting that this change may be responsible for the observed Cl secretion (19 T4. This has been ascribed to a propylthiouracil effect on thyroid metabolism (28,29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With respect to Na transport and IS.,) these findings agree withl previous in vivo observations on rat ileum (2). A comiparable in vitro study with rat ileum (20) differs with both in vivo rat data and our in vitro rabbit data; although MP treatment was found to increase net Na absorption, it was also found to stimulate net Cl secretion; MP treatment was also reported to increase mucosal cGMP concentration, suggesting that this change may be responsible for the observed Cl secretion (19 T4. This has been ascribed to a propylthiouracil effect on thyroid metabolism (28,29).…”
Section: Discussionsupporting
confidence: 92%
“…As shown in Table IIIB ECST has been previously shown to inhibit Na and Cl absorption in rabbit ileum, probably as a result ofan (19) and stimulates Cl secretion in vitro (20). Because cGMP has been postulated to mediate the action of ECST (11,17,18), it was suggested that the above two effects of MP treatment are causally related.…”
Section: Resultsmentioning
confidence: 96%
“…High doses of other glucocorticoids have trophy and hyperplasia in rats with diabetes (23)(24)(25)(26). This hyalso been shown to increase Na,K-ATPase activity in rat small perplasia is also seen in renal tubules (21,47) but not in a intestine (9,57,58). As for K+, only extreme changes incomnumber of other organs tested.…”
Section: Resultsmentioning
confidence: 82%
“…The effects of mineralocorticoids and glucocorticoids on intestinal water and ion movements are well known. Methylprednisolone for 3 days increased Na + K + adenosinetriphosphatase activity and Na + absorption [83]; it also increased guanylate cyclase activity and Cl -secretion in the jejunum and ileum 6 h after administration [84,85]. However, there is no direct information about the increase of water and ion secretion related with increased glucocorticoid secretions in different stressful conditions.…”
Section: Fluid and Ion Secretionmentioning
confidence: 99%